Home renovation - Ching, Frank (Van Nostrand Reinhold Co., 1983)
Home Renovation Frank Ching & Dale E. Miller How to transform your home into a more functional, comfortable, and pleasing environment is fully explained here and illustrated by Frank Ching’s delightful graphics. Far more than a "project" book, this guide melds useful construction information with important planning and design ideas that should precede any decision to renovate or remodel your home